The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1809-29502008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco físicos e organizacionais associados a distúrbios osteomusculares relacionados ao trabalho na indústria têxtil

Abstract: Distúrbios osteomusculares relacionados ao trabalho (DORT) atingem trabalhadores de diversas ocupações e constituem um dos maiores problemas de saúde em muitos países. Este estudo foi realizado em dois setores de fiação de uma mesma indústria têxtil, sendo um deles tecnologicamente mais moderno. Os objetivos foram identificar os fatores de risco físicos e organizacionais associados aos DORT nos dois setores e determinar a prevalência de sintomas de dor entre esses trabalhadores. Tendo como referencial a anális… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
4
0
6
Order By: Relevance
“…These same authors discuss that the presence of pain in this age group may be associated to work and working conditions of these people 7 . Studies point to the relationship between chronic pain and ergonomic factors of work, such as repeatability, manual handling of weight and inadequate postures [8][9][10] . There are also evidences that pain onset or maintenance are associated to organizational and psychosocial factors, such as long working hours, high demand, pressure for time and productivity and social working environment [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…These same authors discuss that the presence of pain in this age group may be associated to work and working conditions of these people 7 . Studies point to the relationship between chronic pain and ergonomic factors of work, such as repeatability, manual handling of weight and inadequate postures [8][9][10] . There are also evidences that pain onset or maintenance are associated to organizational and psychosocial factors, such as long working hours, high demand, pressure for time and productivity and social working environment [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Os fatores organizacionais e psicossociais do trabalho são reconhecidamente associados às LER/ DORT, independente do setor industrial (MELZER, 2008).…”
Section: Introductionunclassified
“…According to the Brazilian Ministry of Health [3] , the textile industry ranks fifth in WRMSD cases. Corroborating this statistic, the present study found that exposure to occupational risk factors is perceived as a serious problem by the workers and is related to regions with a higher incidence of musculoskeletal complaints.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Social Security Agency defines WRMSD as a clinical syndrome involving a variety of inflammatory and degenerative morbidities that affect the musculoskeletal system, particularly in the spinal region and upper limbs [3] . The condition is characterized by the presence of musculoskeletal Work 41 (2012) 2445-2448 DOI: 10.3233/WOR-2012-0478-2445 IOS Press symptoms, compensatory posture changes and temporary or permanent functional disabilities [12] .…”
Section: Introductionmentioning
confidence: 99%